A tetranuclear calcium hydride cluster with a highly symmetric [Ca4H6]2+ core. Issue 98 (25th November 2019) - Schuhknecht, Danny; Spaniol, Thomas P.; Douair, Iskander; Maron, Laurent; Okuda, Jun
Abstract : The NNN-type macrocycle Me3 TACN stabilizes a highly symmetric calcium hydride with a tetranuclear [Ca4 H6 ] 2+ core. It can be classified as a nido -cluster with a highly delocalized system including d-orbital contribution. Abstract : A highly symmetric, dicationic tetranuclear calcium hydride cluster with an adamantoid [Ca4 H6 ] 2+ core stabilized by the NNN macrocycle Me3 TACN (1, 4, 7-trimethyl-1, 4, 7-triazacyclononane) was prepared. DFT calculations indicate delocalized bonding within the [Ca4 H6 ] 2+ fragment with d-orbital contribution.